Allium dönmezii, a new species of Allium sect. Melanocrommyum (Amaryllidaceae) from Turkey: morphological and molecular evidence - Karakuş, Şükrü; Mutlu Bi̇rol (Phytotaxa, 2019)
Allium dönmezii is described as a new species from east Anatolia, Turkey. The molecular marker ITS (Internal Transcribed Spacer of nuclear ribosomal DNA) confirms that the new species belongs to A. sect. Melanocrommyum. The diagnostic characters of the new species are morphologically compared with the related A. woronowii, A. serpentinicum, and A. moderense, as well as with A. rothii and A. chrysantherum. In addition, the ITS regions of A. purpureoviride and A. chrysantherum were sequenced and uploaded on GenBank for the first time.